Azithromycin Differentially Alters TCR-Activated Helper T Cell Subset Phenotype and Effector Function - Ansari, Abdul Wahid; Sharif-Askari, Fatemeh Saheb; Jayakumar, Manju Nidagodu; Mohammed, Abdul Khader; Sharif-Askari, Narjes Saheb; Venkatachalam, Thenmozhi; Mahboub, Bassam; Schmidt, Reinhold E.; Hamoudi, Rifat Akram; Halwani, Rabih; Hamid, Qutayba (Frontiers in Immunology, 2020)
In addition to their antibiotic activities, azithromycin (AZM) exhibits anti-inflammatory effects in various respiratory diseases. One of the potent anti-inflammatory mechanisms is through inhibition of CD4+ helper T (Th) cell effector function. However, their impact on specific Th subset is obscure. Herein, we demonstrate the cellular basis of phenotypic and functional alterations associated with Th subsets following AZM treatment in vitro. Using well-characterized Th subset specific chemokine receptors, we report significant suppression of T cell receptor (TCR)-stimulated hyperactivated CCR4+CXCR3+ (Th0) expansion compared to CCR4-CXCR3+ (Th1-like) and CCR4+CXCR3- (Th2-like) cells. Interestingly, this effect was associated with diminished cell proliferation. Furthermore, AZM significantly inhibited the inflammatory cytokines IFN- and IL-4 production, CCR4 and CXCR3 receptor expression, and viability of Th0, Th1-like and Th2-like subsets. Our findings suggest that AZM differentially affects TCR-activated Th subsets phenotype and function, and CCR4 and CXCR3 downregulation and suppressed Th0 subset expansion could potentially influence their trafficking and differentiation into cytokine-producing effector cells.